Competencies of Teachers in Physical Education Programs of Higher Education Institutions in Region 10 - T. MIGUEL, CESAR (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This study assessed the level of competencies of teachers in Physical Education Programs of HEis in Region J!O. Ten HEis in Region 10 comprised the institutional samples while 56 teachers r,espondents. A paper-and-pencil test and a questionnaire were used to gather data. Frequency, percent distribution, the mean, and two non-parametric tests, tested at .05 and .01 levels of significance, were used to analyze the data. The findings showed that the PE teachers had poor teaching competencies in content knowledge but were found to have very good competencies in both professional and pedagogical skills. The over-all teaching competency level obtained was satisfactory signifying that the said teachers met the minimum local and global standards required,. Of the teacher characteristics, only age was found not to be associated with competencies in content knowledge while 3 and 6 variables we11e found to be si§IJ.ificantly associated with pedagogical and professional skills, respecfarely. As to differences in content knowledge competencies, 3 variables were found to be significant. Seven variables brought significant differences to scores in pedagogical teaching competency skills while only educational attainment was found t0 bring significant differences in professional competency skills.